Comparing Hemodynamic Responses to Intubation in Hypertensive Patients: Clearvue® Video Laryngoscope Versus Macintosh Direct Laryngoscope - Vyas, Ram Kishan; Meena, Sunita; Sharma, Jai; Sompura, Ritesh Kumar (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: The ClearVue® video-laryngoscope (CVL) is believed to alleviate the stress response associated with intubation by providing superior laryngeal views, minimizing oropharyngo-laryngeal stimulation, and potentially reducing the pressor response. Objective: This study aims to assess and compare how effective and safe intubation is when using a CVL versus a Macintosh direct laryngoscope (MDL) in patients with high blood pressure who are having surgery. Methods: This prospective, randomized, interventional study was conducted on 140 hypertensive patients on antihypertensive medication undergoing elective surgery under general anesthesia (GA), who were allocated into two groups, CVL group (n = 70) and MDL group (n = 70). Hemodynamic parameters, including mean arterial pressure (MAP), mean heart rate (HR), systolic blood pressure (SBP), and diastolic blood pressure (DBP), were monitored at baseline, induction, and at various intervals post-intubation (1, 2, 3, 4, 5, and 10 minutes). Other metrics, such as intubation time, intubation attempts, ease of intubation, and associated complications, were documented. Results: Significant differences in heart rate were observed between the groups, right at intubation and at 1, 2, and 3 minutes post-intubation (p-values: 0.011; 0.028; 0.002; 0.003). SBP showed significant differences at intubation and during the first four minutes post-intubation (p-values < 0.001 except for the fourth minute, p = 0.001). DBP and MBP also showed significant differences at various intervals post-intubation (p-values < 0.001 to 0.025 and < 0.001 to 0.020, respectively). No significant difference in airway complications was noted. Conclusion: The CVL offers advantages over MDL in patients with controlled hypertension, specifically in reducing hemodynamic changes during intubation without increasing airway complications. At the same time, MDL offered less intubation time overall than CVL.